2016
DOI: 10.1113/jp272950
|View full text |Cite
|
Sign up to set email alerts
|

Progressive impairment of cerebellar mGluR signalling and its therapeutic potential for cerebellar ataxia in spinocerebellar ataxia type 1 model mice

Abstract: Key pointsr Spinocerebellar ataxia type 1 (SCA1) is a progressive neurodegenerative disease caused by a gene defect, leading to movement disorder such as cerebellar ataxia.r It remains largely unknown which functional defect contributes to the cerebellar ataxic phenotype in SCA1.r In this study, we report progressive dysfunction of metabotropic glutamate receptor (mGluR) signalling, which leads to smaller slow synaptic responses, reduced dendritic Ca 2+ signals and impaired synaptic plasticity at cerebellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 80 publications
(354 reference statements)
5
65
0
Order By: Relevance
“…Power et al reported that blockade of astroglial glutamate transporters, which markedly enhances the amplitude and the duration of mGluR1-mediated slow EPSPs in control mice, had no effect in the SCA1 82Q mouse line 84 . This result suggests that glutamate uptake by Bergmann glia may be severely impaired in the SCA1 82Q mouse line used by Power et al and, therefore, mGluR1-mediated slow EPSPs may be prolonged, even though mGluR1 signaling itself might be impaired in Purkinje cells similarly to those of the SCA1 Tg-B05 line used by Shuvaev et al 81 …”
Section: Dysregulation Of Mglur1 Signaling In Purkinje Cells In Cerebmentioning
confidence: 90%
See 4 more Smart Citations
“…Power et al reported that blockade of astroglial glutamate transporters, which markedly enhances the amplitude and the duration of mGluR1-mediated slow EPSPs in control mice, had no effect in the SCA1 82Q mouse line 84 . This result suggests that glutamate uptake by Bergmann glia may be severely impaired in the SCA1 82Q mouse line used by Power et al and, therefore, mGluR1-mediated slow EPSPs may be prolonged, even though mGluR1 signaling itself might be impaired in Purkinje cells similarly to those of the SCA1 Tg-B05 line used by Shuvaev et al 81 …”
Section: Dysregulation Of Mglur1 Signaling In Purkinje Cells In Cerebmentioning
confidence: 90%
“…Power et al recently reported that the SCA1 82Q mouse line generated by Zu et al 79 , which is different from the SCA1 Tg-B05 line originally generated by Burright et al 72 and used in the recent study by Shuvaev et al 81 , exhibits reduced motor performance in the rotating rod, reduced complexity of Purkinje cell outer dendrites, decreased height of climbing fiber innervation, and lower frequency of Purkinje cell simple spike firing at 12 weeks of age 84 ( Table 2). In contrast to the report by Shuvaev et al 81 , mGluR1-mediated slow EPSCs and local Ca 2+ transients in dendrites induced by repetitive parallel fiber stimulation were both prolonged in SCA1 82Q Purkinje cells without significant changes in their amplitudes 84 . Remarkably, administration of a negative allosteric modulator (NAM) of mGluR1 shortened the two forms of mGluR1-mediated synaptic responses and ameliorated the ataxia 84 .…”
Section: Dysregulation Of Mglur1 Signaling In Purkinje Cells In Cerebmentioning
confidence: 91%
See 3 more Smart Citations